PENYUSUNAN MODEL SIMULASI TANAMAN JARAK (Richinus communis L.)CONSTRUCTION OF A CROP SIMULATION MODEL OF CASTOR OIL (Richinus communis L.) - Fadjry Djufri; I Handoko; Justika Baharsjah; Yonny Koesmaryono; Didiek H. Goenadi (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2004)
Abstract is available in the full text (pdf format)